Porosity and Permeability Modifications by Diagenetic Processes in Fossiliferous Sandstones of the West Baram Delta, Offshore Sarawak - Ben-Awuah, Joel (2014)
Baram Delta is the most prolific hydrocarbon province of all the geological provinces in the Sarawak Basin. Major fossilferous intervals have been identified within these units. The objective of this paper is to investigate the impact of diagenetic processes on fossils in fossilferous sandstones and how such modifications to fossils influence porosity and permeability. Seven wells from four fields in the Baram delta were evaluated using thin sections, CT scan imaging, SEM, EDX, spot permeability, core plug porosity and permeability measurements. Intragranular pores have been formed within fossils by dissolution of fossils. The formation of these pores has been facilitated by uplift of the Rajang Group accretionary prism to form the Rajang Fold-Thrust Belt. An increase in porosity and permeability is observed in both spot permeability and core plug porosity and permeability measurements in the fossilferous sandstones. Spot permeability in fossilferous part of the sandstones range between 606mD-879mD whereas the non fossilferous part has spot permeability values ranging between 305-521mD. This represents a permeability enhancement of 50-60% in the fossilferous part. Core plugs from the fossilferous horizons have porosity between 18-30% and permeability ranging between 662mD-683mD whereas the non fossilferous horizons have porosity between 13-27% and permeability ranging between 10-529mD.